The secrets of the abbey - Bannalec, Jean-Luc, 1966- (Bannalec, Jean-Luc, 1966- Brittany mystery, 2026)
"In international bestselling author Jean-Luc Bannalec's The Secrets of the Abbey, between large inlets, the wild Atlantic, and enchanting apple orchards, a tricky and highly personal case unfolds for Commissaire Georges Dupin and his team. Summer in Brittany has carried merrily into October, bringing warm, sunny days and balmy nights. For Commissaire Georges Dupin and his team, it also brings a heavy blow. Second inspector Kadeg's aunt has passed away after being struck by a series of omens of death. And when Kadeg travels to the former abbey where his aunt lived, he's attacked and critically injured. Dupin and the rest of his team quickly head to the aunt's estate on the Côte des Légendes to look into what happened. But the more they look, the more questions are uncovered, and the more secrets Kadeg's family seems to have"-- Provided by publisher.